Examining the impacts of urban, work and social environments on residents’ subjective wellbeing: a cross-regional analysis in China - Fang, Zhou; Liao, Yuxin; Ma, Chang; Wu, Rong (Frontiers in Environmental Science, 2024)
Urbanization has affected the quality of the living environment. It is important to improve residents' living environments and promote their happiness. Using the data from the 2018 China Labor-force Dynamics Survey, this study examines impacts of the urban, work and social environments on the residents' subjective wellbeing (SWB) using a linear regression model. In addition, the 8396 resident samples were randomly selected nationwide. The three major findings are as follows: (1) At the national level, residents' SWB exhibits a notable spatial variability, being higher in the northern regions and lower in the southern areas. (2) The dimensions of the urban environments (housing prices, POI density, NPP, land development intensity and the number of tertiary hospitals), the work environments (work pressure and job satisfaction), and the social environments (community trust, social justice and sense of security), along with sociodemographic characteristics, significantly influence SWB. (3) In China, the impacts on SWB exhibit pronounced regional heterogeneity. The relationship between environmental pollution and SWB is characterized by an inverted U-shaped pattern. Intriguingly, while housing prices negatively affect SWB in the eastern and central regions, the enforcement of housing purchase limits has been observed to enhance residents ' SWB in the western region.